COMMUNITY PARTICIPATION ON WASTEWATER TREATMENT PLANT DEVELOPMENT IN BAJERA VILLAGE - I Gede Adnyana; I Wayan Gde Wiryawan; Sang Putu Kaler Surata; I Ketut Sumantra (International Journal of Applied Science and Sustainable Development (IJASSD), 2020)
The concept of community-based wastewater management is currently considered an appropriate concept in carrying out a sanitation facility development program, especially domestic wastewater treatment facilities. Therefore, through the Community-Based Total Sanitation program by constructing communal wastewater treatment plants (WWTP) using the Community Based Participatory Research pattern, it is hoped that the pattern of handling sanitation problems in Bajera Village can be more optimal, from planning, development to management and monitoring. The objective to be achieved in this research is to formulate a participatory Communal WWTP development strategy in accordance with the level of community needs in Bajera Village. This research design uses qualitative methods by involving field participants and validation participants. Data collection techniques using open questionnaires, semi-structured interviews, and FGD. After analyzing the data using the Interpretative Phenomenological Analysis (IPA) method, the strategies carried out through social engineering are: (1). Conduct education through integrated outreach by involving relevant regional authorities. (2). Involving traditional leaders, religious leaders, youth leaders, women leaders, and migrant communities starting from the planning, development, management, and monitoring stages. (3). Make awig-awig and village regulations on wastewater management which are then used as the basis for regularity in community life so that a clean and healthy environment is formed.